HIV Type 1 Infection Up-Regulates TLR2 and TLR4 Expression and Function in Vivo and in Vitro (2012)
ABSTRACT: Toll-like receptors (TLRs) play a critical role in innate immunity against pathogens. Their stimulation induces the activation of NF-κB, an important inducer of HIV-1 replication. In recent years, an increasing number of studies using several cells types from HIV-infected patients indicate that TLRs play a key role in regulating the expression of proinflammatory cytokines and viral pathogenesis. In the present study, the effect of HIV-1 stimulation of monocyte-derived macrophage (MDM) and peripheral blood mononuclear cell (PBMC) subpopulations from healthy donors on the expression and functions of TLR2 and TLR4 was examined. In addition, and to complete the in vitro study, the expression pattern of TLR2 and TLR4 in 49 HIV-1-infected patients, classified according to viral load and the use of HAART, was determined and compared with 25 healthy subjects. An increase of TLR expression and production of proinflammatory cytokines were observed in MDMs and PBMCs infected with HIV-1 in vitro and in response to TLR stimulation, compared to the mock. In addition, an association between TLR expression and up-regulation of CD80 in plasmacytoid dendritic cells (pDCs) was observed. The ex vivo analysis indicated increased expression of TLR2 and TLR4 in myeloid dendritic cells (mDCs), but only of TLR2 in monocytes obtained from HIV-1-infected patients, compared to healthy subjects. Remarkably, the expression was higher in cells from patients who do not use HAART. In monocytes, there was a positive correlation between both TLRs and viral load, but not CD4(+) T cell numbers. Together, our in vitro and ex vivo results suggest that TLR expression and function can be up-regulated in response to HIV-1 infection and could affect the inflammatory response. We propose that modulation of TLRs represents a mechanism to promote HIV-1 replication or AIDS progression in HIV-1-infected patients.